KETERAMPILAN KOMUNIKASI EFEKTIF, KOMUNIKASI TERBUKA DAN JELAS DALAM MICRO LEADING - Ramadhan, Muhammad Aryo; Mufid, Dyonel Ilham; Ilham, Rahmat; Tarigan, Sry Wahyana Br; Bangun, Gladis Salsabilla; Andriani, Tuti (STKIP Pesisir Selatan, 2025)
A common phenomenon in micro-leadership practices across various work environments is poor communication between leaders and team members. Many leaders fail to recognize the importance of open and honest two-way communication and lack the skills to convey instructions or expectations clearly. This study aims to examine in depth how effective communication skills, open communication, and clear communication play a role in supporting the practice of micro leadership (micro leading). The research method used is a literature study, by analyzing various scientific sources, including reference books and national as well as international journal articles relevant to the topic. The findings indicate that effective communication includes the ability to deliver messages accurately, empathetically, and to build two-way dialogue. Open communication creates a participatory space that fosters trust and psychological safety within the team. Meanwhile, clear communication ensures that each member understands their roles, tasks, and expectations accurately. These three aspects support one another and form an essential foundation for the success of micro leadership in building a solid, adaptive, and productive team.